2007
DOI: 10.1080/01446190701567413
|View full text |Cite
|
Sign up to set email alerts
|

Communication behaviour during management and design team meetings: a comparison of group interaction

Abstract: Although a few studies have investigated the communication behaviour of construction professionals this research represents the first attempt to model the construction team's interaction in live project meetings. Using the established Bales interaction process analysis (IPA) method, both task and relational interaction were recorded and a model of group communication was produced. A total of 36 meetings were observed from 10 construction projects and the data aggregated to provide a single profile of the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 10 publications
0
36
1
Order By: Relevance
“…In the traditional procurement process, project teams are formed on an ad-hoc basis. Gorse and Emmitt (2007) found that 'work environment' and 'working relationship' among project teams has an influence on the effectiveness of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Goodwin, 1993;Bowles et al, 2001;Stein et al, 2005).…”
Section: Factor 2: Credibility and Background Factormentioning
confidence: 99%
“…In the traditional procurement process, project teams are formed on an ad-hoc basis. Gorse and Emmitt (2007) found that 'work environment' and 'working relationship' among project teams has an influence on the effectiveness of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 (Goodwin, 1993;Bowles et al, 2001;Stein et al, 2005).…”
Section: Factor 2: Credibility and Background Factormentioning
confidence: 99%
“…As a consequence, in the state of Victoria it has been common practice for design teams to assess and attempt to design out OHS risks relating to the operation stage of a facility but not consider the health and safety of construction workers in the same risk management process. Gorse and Emmitt (2007) identify the need to investigate social interaction and communication in 'live' construction projects. In-keeping with this recommendation, the data collection approach adopted involved a number of different methods including: (i) direct observation of project team interactions; (ii) interviews with project actors; and (iii) inspection of artefacts, such as aspects of the physical worksite and project documentation.…”
Section: The Legislative Contextmentioning
confidence: 99%
“…For example, to enable and facilitate participation in sharing inspiration, leveraging expertise and consolidating information, group or teamwork in all kinds of projects is often proposed in meetings (Gallivan and Keil, 2003;Gorse and Emmitt, 2007;Hass, 2006;Wenger et al, 2002). As Orlikowski and Yates (1994) have observed, meetings are also commonly used by organizations to handle ad-hoc types of codified group or team actions.…”
Section: Meetings In Project Managementmentioning
confidence: 98%
“…This is where the importance of conveniently timed and wellplanned meetings enters into the discussion. In all business activities, meetings are an important instrument for group work (Gorse and Emmitt, 2007;Hass, 2006;Wenger et al, 2002). They are the important venue where various stakeholders and parties meet to communicate and collaborate on a project's development.…”
Section: Introductionmentioning
confidence: 97%